High-fat diet-induced obesity triggers alveolar bone loss and spontaneous periodontal disease in growing mice. Issue 1 (December 2015) - Fujita, Yuko; Maki, Kenshi
Abstract Background The relationship between high-fat food consumption and obesity is well-established. However, it is as yet unclear whether high-fat diet (HFD)-induced obesity in childhood and adolescence determines age-related changes in jaw bone health. The aim of this study is to examine the age-related influence of HFD-induced obesity on mandibular bone architecture and the structure of the periodontium in growing mice. Methods Male C57BL/6 J mice (6-weeks-old) were divided into two groups (n = 6 each): the control group received a control diet and the experimental group a HFD. After treatment for 4, 8, or 12 weeks, trabecular and cortical bone architecture was assessed using micro-computed tomography. The periodontium and alveolar bone structure were evaluated by histopathology. Results In HFD mice, body weight, serum total cholesterol, and serum leptin levels were significantly higher than those in age-matched control mice (p < 0.05, all comparisons). Reductions in trabecular bone volume and in cortical bone growth (measured as the thickness and cross sectional area) in HFD mice were significant compared with the control mice after 4 weeks of treatment (p < 0.05, both comparisons). Significant decreases in cortical bone density in HFD-fed vs. age-matched control mice were determined after 12 weeks (p < 0.05). In the HFD mice, the periodontal ligament fibres were disrupted, having lost their orientation with respect to the bone surface, and constriction of the periodontal ligament space was inhibited. Conclusions These results suggest that HFD-induced obesity during growth not only triggers mandibular osteoporosis but also increases the risk of spontaneous periodontal disease.